Fifty years of the Biological Records Centre. (15th June 2015) - Roy, Helen E.; Preston, Christopher D.; Roy, David B.
Abstract: In this special issue of the Biological Journal of the Linnean Society, we celebrate 50 years of the Biological Records Centre (BRC) but, more importantly, we celebrate the pioneers of BRC and the volunteer recording community. It is inspiring to consider the many individuals who have contributed to the rich legacy of biological recording since the 16th Century. The core activity of BRC has remained unchanged since its foundation in 1964: working in partnership with volunteer recording schemes and societies to collate, manage, disseminate, and interpret species observations (biological records). However, innovative technologies and the development of statistical approaches are taking biological recording in new and exciting directions. The large spatial coverage and increasingly fine-scale spatial precision of biological records enable ecologists to examine large-scale processes that would be impossible to address without the contribution of voluntary recorders.